Final girls : a novel - Sager, Riley (New York, New York : Dutton, an imprint of Penguin Random House LLC, 2017)
Emerging as the lone survivor of a serial killer's massacre a decade earlier, Quincy Carpenter struggles to ignore traumatic memories and move on as one of a group of other survivors who look to her for answers when one of them is found dead in a suspicious suicide
Keywords: Victims of violent crimes -- Fiction; Women -- Violence against -- Fiction; Survival -- Psychological aspects -- Fiction; Mystery fiction; Suspense fiction; Detective and mystery fiction; Thrillers (Fiction)